COSTA-KALLICK'S HABITS OF MIND IN PRACTICAL ACTIVITIES OF STUDENTS AS BIOLOGY’S TEACHER CANDIDATES - Ria Yulia Gloria; Sudarmin .; Wiyanto .; Dyah Rini Indriyanti (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2018)
COSTA-KALLICK’S HABITS OF MIND DALAM KEGIATAN PRAKTIKUM PADA MAHASISWA CALON GURU BIOLOGIAbstract The purpose of education is not only to improve thinking ability but also to form habits of mind. Therefore it is important to form ideal habits of mind. One of lessons that is often accepted by prospectivebiology teacher is practicum. The problem is whether the practicum is able to form students’shabits of mind? In this study an analysis is conducted of whether the practicum which is obtained by prospective biology teachers can form students’shabits of mind. The method is survey method with 100 students who have been following the practicums for 5 semesters. Data obtained through questionnaire ofCosta and Kallick’shabits of mind which contains 16 categories. The result is 85% of students have habits of mind with strong criteria, 13% very strong criteria, and 2% have enough criteria. And also, 75% of students have strong criteria, 12.5% ​​have enough criteria, and 12.5% ​​have very strong criteria. Very strong criteria is belong to habits of mind categorystriving for accuracy and interdependently thinking. Abstrak Tujuan pendidikan bukan hanya untuk meningkatkan kemampuan berpikir tetapi juga untuk membentuk kebiasaan atau karakter berpikir cerdas (habits of mind). Oleh karena itu perlu upaya untuk melatih agar terbentuk habits of mind yang ideal. Salah satu pembelajaran yang sering diterima oleh mahasiswa calon guru biologi adalah pembelajaran praktikum. Permasalahannya adalah apakah praktikum yang diterima oleh mahasiswa mampu membentuk habits of mind mahasiswa? Pada penelitian ini dilakukan analisis mengenai apakah praktikum yang diperloleh oleh mahasiswa calon guru biologi dapat membentuk habits of mind mahasiswa. Metode yang digunakan adalah metode survey dengan partisipan sebanyak 100 mahasiswa yang telah mengikuti praktikum setiap selama 5 semester. Data diperoleh melalui instrumen berupa angket habits of mind dari Costa dan Kallick yang memuat 16 kategori. Dari 16 kategori sebanyak 85% mahasiswa memiliki habits of mind dengan kriteria kuat, 13% kriteria sangat kuat, sisanya 2% memiliki kriteria cukup. Dari 16 kategorihabits of mind, 75% memiliki kriteria Kuat, 12,5% memiliki kriteria cukup, dan 12,5% memiliki kriteria sangat kuat. Kriteria sangat kuat dimiliki oleh kategori habits of mind striving for accuracy dan thinking interdependently. Permalink/DOI: http://dx.doi.org/10.15408/es.v10i1.7208